Writing a new society social change through the novel in Malay - Hooker, Virginia Matheson 1946- (Southeast Asia publications series, 2000)
An exploration of the novel in Malay and the relationship between social change and literary practice. It traces the emergence of the genre from the 1920s and, drawing on 26 of Malaysia's best-known novels, argues that the form was developed as a vehicle for Malay ideas about their society